2011
DOI: 10.1159/000280318
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Atrophy and Intestinal Metaplasia before and after Helicobacter pylori Eradication: A Meta-Analysis

Abstract: Objective: Whether gastric atrophy (GA) and intestinal metaplasia (IM) are reversible after the eradication of Helicobacter pylori remains controversial. The purpose of this meta-analysis was to systematically review histological alterations in GA and IM by comparing histological scores before and after H. pylori eradication. Methods: English-language articles in the medical literature containing information about the association between infection with H. pylori and gastric premalignant lesions (i.e. GA and IM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
129
4
14

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(152 citation statements)
references
References 63 publications
(35 reference statements)
5
129
4
14
Order By: Relevance
“…Although H. pylori is well known to be associated with development of atrophic gastritis, intestinal metaplasia, and gastric cancer, there is no clear evidence that intestinal metaplasia is improved by H. pylori eradication [20,21]. It seems that once intestinal metaplasia develops, H. pylori eradication cannot prevent malignant progression.…”
Section: Discussionmentioning
confidence: 99%
“…Although H. pylori is well known to be associated with development of atrophic gastritis, intestinal metaplasia, and gastric cancer, there is no clear evidence that intestinal metaplasia is improved by H. pylori eradication [20,21]. It seems that once intestinal metaplasia develops, H. pylori eradication cannot prevent malignant progression.…”
Section: Discussionmentioning
confidence: 99%
“…A key issue in establishing gastric cancer prevention strategies is to define the exact point within the evolutionary cascade of chronic gastritis from which regression of histological changes after eradication of the microorganism is no longer observed. Although controversial, due to possible sampling errors, a recent meta-analysis suggests that atrophic gastritis of the corpus can reverse after H pylori eradication (203) .…”
Section: Statement 14mentioning
confidence: 99%
“…This can be explained by the smaller number of gastric glands in the normal antral mucosa (18,152) . The results of H pylori eradication on atrophic gastritis are often controversial (38,102,111,203) . A recent meta-analysis study involving 12 trials analyzing 2,648 patients with atrophic gastritis of the antrum found no significant reversibility of atrophic changes in the antrum following H pylori eradication (203) .…”
Section: Statement 15mentioning
confidence: 99%
See 1 more Smart Citation
“…Мета-анализ 12 исследований (2658 больных) показал, что устранение H. pylori способствует выраженному уменьшению атрофии в теле же-лудка, но не в антральном отделе, и не оказыва-ет влияния на кишечную метаплазию [17]. Вот почему консенсус «Маастрихт-4» отмечает, что наилучшие результаты канцеропревенции до-стигнуты в группе больных, у которых эрадика-ция H. pylori проводилась до появления первых признаков атрофии СОЖ.…”
unclassified